Counselling the stressed for psychological wellbeing - Chirnga, Randall; Abdullah, Haslee Sharil Lim; Madon, Zainal; Lau, Poh Li (Universiti Sains Islam Malaysia, 2016)
The political, social and economic milieu in Malaysia has put many people in tight situations to make ends meet while maintaining their sanity. The struggles and hardships when become chronic will have a negative impact on their psychological wellbeing. The constant and sometimes abrupt changes can throw people off balance and breed stress, anxiety and tension. During this turbulent and uncertain situation, it is believed that counselling services could help the people to manage their life situations amicably despite the adversity faced. Based on extensive literature review, this article deliberates on the stressors, counselling philosophy and ways counselling services could contribute in helping people to pull through their difficult and challenging situations and at the same time monitor and maintain their mental health level. It is believed that the deliberations have contributed to the understanding of counselling services in Malaysia that should be fully utilized by those in need of the services.